VOICE SIGNAL SYNTHESIS FOR CORRECTION OF HUMAN PSYCHOPHYSIOLOGICAL STATE - Muhamadiev A.; Isvandiyarova M. (Journals Park Publishing, 2023)
This work is devoted to the audio signal synthesis software package for the correction of human psychophysiological condition. In order to ensure the synthesis of the sound effect of the required frequency, it is necessary to conduct a spectral analysis of the original bioelectrical signal, to determine the local extrema of the resulting spectral function, and to calculate the required frequency of the sound effect according to the obtained extrema. Synthesis of the spectral function and the sound effect of the desired frequency.
Keywords: Algorithm, synthesis, harmonic sound, Fourier transform, spectral analysis, spectrum extremes, multiple frequencies, software package.